Management of Stable COPD: An Update - Corlateanu, Alexandru; Montanari, Gloria; G. Mathioudakis, Alexandros; Botnaru, Victor; Siafakas, Nikolaos (Current Respiratory Medicine Reviews, 2013)
Chronic Obstructive Pulmonary Disease (COPD), being a major cause of morbidity and mortality worldwide, is a major problem for public health. It is predicted that its burden will continuously expand over the next years. This article is an up-to-date review of both non-pharmacologic and pharmacologic management of COPD, which is now based on new staging systems, able to predict prognosis and the response to different treatment approaches. Non-pharmacologic therapies, such as smoking cessation, vaccinations and pulmonary rehabilitation are covered briefly. Current pharmacologic management covers short acting beta-agonists (SABA), short acting muscarinic antagonists (SAMA), long acting beta agonists (LABA), long acting antimuscarinics (LAMA), inhaled corticosteroids (ICS), LABA/ICS combinations, xanthines, specific phosphodiesterase 4 (PDE4) inhibitors and oxygen therapy.
Keywords: Chronic obstructive pulmonary disease (COPD)